A pre-sodiated hard carbon negative electrode material, a preparation method therefor and an application thereof

CN116598488BActive Publication Date: 2026-10-27SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310792391.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2026-10-27
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

[0005]本发明的一个目的在于提供一种预钠化硬碳负极材料的制备方法,以解决现有技术存在的首效改善不明显、动力学性能差及循环寿命差的问题;本发明的制备方法简单,成本低,得到的预钠化硬碳负极材料具有首效高、动力学性能优异的特点,且在大倍率快速充电下还能兼具循环寿命长的特点

Benefits of technology

[0028](1)本发明对硬碳进行预钠化处理,并且可以准确的计算出加入钠源基化合物的质量,以达到预钠首效最大化;再对其进行包覆,钠带正电,碳原子带负电,在高温下,钠源吸附在苯环上的Na+与HC表面带负电荷的含氧官能团和碳缺陷发生反应,生成准金属钠沉积在硬碳表面缺陷中,补偿不可逆的钠吸附;化学形成的钠在电解质中预钠化硬碳材料上形成强大的富含NaF的SEI,它促进了界面反应动力学和可逆的Na+插入和脱出,可极大地提高硬碳材料首次充放电效率;碳包覆层可阻碍钠与外界的直接接触,增强材料的稳定性,提高材料的导电性能和动力学性能,同时也可改善循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116598488B_ABST
    Figure CN116598488B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a pre-sodiumized hard carbon negative electrode material and a preparation method and application thereof. The preparation method of the pre-sodiumized hard carbon negative electrode material comprises the following steps: uniformly mixing resin and an alcohol solvent, and then heating to obtain a cured resin; performing ball milling treatment on the cured resin and a sodium source-based compound to obtain a precursor; performing carbonization treatment on the precursor to obtain a carbonized material; and performing heat treatment on a mixed system of the carbonized material and a gaseous carbon source to obtain the pre-sodiumized hard carbon negative electrode material. The preparation process is simple, the cost is low, the obtained pre-sodiumized hard carbon negative electrode material has the characteristics of high initial efficiency and excellent kinetic performance, and still has a long cycle life under large-rate rapid charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a pre-sodium-modified hard carbon anode material, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries possess advantages such as high energy density, excellent cycle performance, and long lifespan, leading to their widespread application in portable electronics, electric vehicles, and large-scale energy storage. However, the scarcity of lithium resources on Earth and the difficulty of extraction have resulted in increasingly high costs for lithium salts, making the development of low-cost, high-performance novel electrochemical energy storage technologies an urgent priority.

[0003] Sodium, due to its abundant resources, uniform global distribution, and physicochemical properties similar to lithium, makes low-cost, high-performance sodium-ion batteries an ideal alternative to lithium-ion batteries. The development of key electrode materials for sodium-ion batteries is currently a research hotspot. Compared to lithium-ion batteries, sodium ions have an atomic radius at least 35% larger than lithium ions. The pore size and interlayer spacing of graphite anode materials used in lithium-ion batteries cannot meet the requirements of sodium-ion battery anodes, making them unsuitable for use as sodium-ion battery anode materials. Hard carbon materials possess advantages such as large interlayer spacing, diverse structures, low cost, good conductivity, high sodium storage capacity, small volume deformation after sodium intercalation, environmental friendliness, and low redox potential, making them the mainstream anode material route for current sodium-ion batteries. Hard carbon has a disordered internal crystal arrangement, more pores, and sodium can be stored in the interlayers, closed micropores, surface, and defect sites of graphite sheets, resulting in high capacity. Hard carbon is composed of bent, randomly oriented, and defective carbon layers, possessing five / seven-membered carbon rings and oxygen-containing functional groups on the surface, such as hydroxyl and carboxyl groups. However, the numerous structural defects and sodiumification of oxygen-containing functional groups within hard carbon are irreversible, resulting in irreversible capacity loss during the initial cycle. This leads to low coulombic efficiency (60%-85%) and poor cycling performance in hard carbon batteries, severely impacting their application in full-cell batteries. Currently, researchers have focused on reducing irreversible capacity loss in sodium-ion batteries through material structure and electrolyte design, but irreversible sodium consumption remains difficult to eliminate completely.

[0004] In view of this, the present invention is hereby proposed. Summary of the Invention

[0005] One objective of this invention is to provide a method for preparing a pre-sodium-modified hard carbon anode material to solve the problems of insignificant improvement in initial efficiency, poor kinetic performance, and poor cycle life in the prior art. The preparation method of this invention is simple and low in cost, and the resulting pre-sodium-modified hard carbon anode material has the characteristics of high initial efficiency and excellent kinetic performance, and also has the characteristics of long cycle life under high-rate fast charging.

[0006] Another object of the present invention is to provide the aforementioned pre-sodium hard carbon anode material, which has excellent electrochemical and kinetic properties.

[0007] Another object of the present invention is to provide a negative electrode.

[0008] Another object of the present invention is to provide a battery.

[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:

[0010] A method for preparing a pre-sodium-modified hard carbon anode material includes the following steps:

[0011] The resin and alcohol solvent are mixed and heated to obtain a cured resin; the cured resin and sodium-based compound are ball-milled to obtain a precursor; the precursor is carbonized to obtain a carbonized material; the mixture of the carbonized material and a gaseous carbon source is heat-treated to obtain a pre-sodium-modified hard carbon anode material.

[0012] In one embodiment, the resin includes at least one of epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, melamine-formaldehyde resin, furan resin, polyamide resin, acrylic resin, polyurethane, and vinyl resin.

[0013] In one embodiment, the sodium-based compound includes at least one of sodium naphthalene, sodium biphenyl, sodium phenanthrene, sodium benzophenone, disodium terephthalate, and sodium conjugated aromatic diamine.

[0014] In one embodiment, the ratio of the resin to the alcohol solvent is (100-200) g : (480-520) mL.

[0015] In one embodiment, the mass of the sodium source compound is M1 g, the mass of the resin is M2 g, the mass percentage of oxygen-containing functional groups in the resin is W, the heat treatment temperature is T °C, and the heat treatment time is H h. M1, M2, W, T, and H satisfy the following relationship: 0 ≤ M1 - (M2 * 0.2 * H * W / (lg T - 1)) ≤ 5, where 20% ≤ W ≤ 80%, 600 ≤ T ≤ 900, and 1 ≤ H ≤ 5.

[0016] In one embodiment, the mixing time is 3 to 5 hours.

[0017] In one embodiment, the heating temperature is 150–180°C, and the heating time is 2–6 hours.

[0018] In one embodiment, the ball milling process is performed at a rotation speed of 200–600 r / min, and the ball milling process is performed for 1–2 h.

[0019] In one embodiment, the carbonization process is carried out under inert gas conditions.

[0020] In one embodiment, the carbonization treatment is carried out at a temperature of 1200–1500°C, a heating rate of 3–5°C / min, and a holding time of 2–5 h.

[0021] In one embodiment, after the carbonization treatment, the carbonized material is further cooled to room temperature.

[0022] In one embodiment, the heat treatment is performed under inert gas conditions.

[0023] In one embodiment, the carbon source includes at least one of carbon black, conductive graphite, VGCF, carbon nanotubes, graphene, and acetylene black.

[0024] A pre-sodium-modified hard carbon anode material is prepared by the aforementioned method for preparing pre-sodium-modified hard carbon anode materials.

[0025] A negative electrode sheet includes either the pre-sodium hard carbon negative electrode material prepared by the aforementioned method or the aforementioned pre-sodium hard carbon negative electrode material.

[0026] A battery comprising the aforementioned negative electrode.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] (1) This invention pre-sodiumizes hard carbon and can accurately calculate the mass of sodium-based compound added to maximize the pre-sodium effect; then it is coated with sodium, which is positively charged and carbon atoms are negatively charged. At high temperature, the sodium source adsorbs Na on the benzene ring. + Reacting with negatively charged oxygen-containing functional groups and carbon defects on the HC surface, quasi-metallic sodium is generated and deposited in the defects of the hard carbon surface, compensating for irreversible sodium adsorption; the chemically formed sodium forms a strong NaF-rich SEI on the pre-sodiumized hard carbon material in the electrolyte, which promotes interfacial reaction kinetics and reversible Na+ adsorption. + Insertion and extraction can greatly improve the initial charge-discharge efficiency of hard carbon materials; the carbon coating can prevent sodium from directly contacting the outside world, enhance the stability of the material, improve its electrical conductivity and kinetic properties, and also improve cycle life.

[0029] (2) The pre-sodium hard carbon anode material of the present invention has excellent electrochemical and kinetic properties.

[0030] (3) The battery of the present invention has excellent first-efficiency, dynamic performance and cycle performance. Attached Figure Description

[0031] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0032] Figure 1 This is a SEM image of the hard carbon anode material in Example 1 of the present invention;

[0033] Figure 2 This is a SEM image of the hard carbon anode material in Comparative Example 1 of the present invention. Detailed Implementation

[0034] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0035] According to one aspect of the present invention, the present invention relates to a method for preparing a pre-sodium-modified hard carbon anode material, comprising the following steps:

[0036] The resin and alcohol solvent are mixed and heated to obtain a cured resin; the cured resin and sodium-based compound are ball-milled to obtain a precursor; the precursor is carbonized to obtain a carbonized material; the mixture of the carbonized material and a gaseous carbon source is heat-treated to obtain a pre-sodium-modified hard carbon anode material.

[0037] In the preparation of hard carbon, this invention involves pre-sodiumizing the hard carbon and accurately calculating the mass of sodium-based compounds added to maximize the initial sodium-sodium effect before coating. Sodium carries a positive charge, while carbon atoms carry a negative charge. At high temperatures, Na+ ions adsorbed on the benzene ring react with negatively charged oxygen-containing functional groups and carbon defects on the HC surface, generating near-metallic sodium that deposits in the surface defects of the hard carbon, compensating for irreversible sodium adsorption. The chemically formed sodium forms a strong NaF-rich SEI on the pre-sodiumized hard carbon material in the electrolyte, which promotes interfacial reaction kinetics and reversible Na+ deposition. + Insertion and extraction can greatly improve the initial charge-discharge efficiency of hard carbon materials; the coating layer can prevent sodium from directly contacting the outside world, which can enhance the stability of the material and improve its electrical conductivity and kinetic properties, while also improving cycle life, thus solving the problems of insignificant improvement in initial efficiency, poor kinetic properties and poor cycle life in existing technologies.

[0038] In one embodiment, the resin includes at least one of epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, melamine-formaldehyde resin, furan resin, polyamide resin, acrylic resin, polyurethane, and vinyl resin. In one embodiment, the resin is selected from any one of the above resins. In one embodiment, the resin is selected from a combination of at least two of the above resins, each resin being of equal mass. In one embodiment, the resin is a phenolic resin and a furfural resin, with a mass ratio of phenolic resin to furfural resin of 1:1. In one embodiment, the resin is selected from melamine-formaldehyde resin, furan resin, and polyamide resin, with a mass ratio of melamine-formaldehyde resin, furan resin, and polyamide resin of 1:1:1.

[0039] In one embodiment, the sodium source compound includes at least one of sodium naphthalene, sodium biphenyl, sodium phenanthrene, sodium benzophenone, disodium terephthalate, and sodium conjugated aromatic diamine. In one embodiment, the sodium source compound is selected from any one of the above-mentioned sodium source compounds. In one embodiment, the sodium source compound is selected from at least two of the above-mentioned sodium source compounds, each sodium source compound having the same mass.

[0040] In one embodiment, the ratio of the resin to the alcohol solvent is (100-200)g:(480-520)mL, for example, 100g:500mL, 150g:500mL, 200:520mL, etc.

[0041] In one embodiment, the mass of the sodium-based compound is M1 g, the mass of the resin is M2 g, the mass percentage of oxygen-containing functional groups in the resin is W, the heat treatment temperature is T °C, and the heat treatment time is H h. M1, M2, W, T, and H satisfy the following relationship: 0 ≤ M1 - (M2 * 0.2 * H * W / (lgT - 1)) ≤ 5, where 20% ≤ W ≤ 80%, 600 ≤ T ≤ 900, 1 ≤ H ≤ 5, and lg is a logarithmic function to base 10. In one embodiment, the value of M1 - (M2 * 0.2 * H * W / (lgT - 1)) is 0.1, 0.3, 0.5, 0.8, 1, 1.5, 1.8, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc. In one embodiment, W is 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc. The heat treatment temperature is 600℃, 650℃, 670℃, 700℃, 720℃, 750℃, 770℃, 800℃, 820℃, 850℃, 870℃, 900℃, etc. The heat treatment time is 1h, 2h, 3h, 4h, or 5h, etc. The quality of the added sodium-based compound is related to the resin quality, heat treatment temperature, time, and the proportion of oxygen-containing functional groups. Adding too much sodium-based compound results in low material utilization and high cost; adding too little will not achieve the optimal pre-sodiumization effect. The residual carbon content of the resin is generally around 20%. The higher the heat treatment temperature, the better. M2*0.2 represents the final mass of hard carbon that can be prepared, multiplied by W to represent the mass of oxygen-containing functional groups. When 0≤M1-(M2*0.2*H*W / (lgT-1))≤5, pre-sodiumization can achieve excellent results. This invention ensures that the pre-sodiumized hard carbon anode material has excellent electrochemical and kinetic performance by limiting M1, M2, W, T, and H to satisfy the above relationship.

[0042] In one embodiment, the mixing time is 3 to 5 hours, for example, 3.5 hours, 4 hours, 4.5 hours, etc., and the resin and alcohol solvent are mixed evenly by stirring.

[0043] In one embodiment, the alcohol solvent includes ethanol.

[0044] In one embodiment, the heating temperature is 150–180°C, such as 150°C, 160°C, 170°C, 175°C, 180°C, etc., and the heating time is 2–6 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours. The resin is cured by a solvothermal reaction caused by heating.

[0045] In one embodiment, the ball milling speed is 200–600 r / min, for example, 200 r / min, 300 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, etc., and the ball milling time is 1–2 h, for example, 1.2 h, 1.5 h, or 1.8 h. By adopting appropriate ball milling speed and time, the reaction between the curing resin and the sodium source compound is more favorable, which is beneficial to the electrochemical and kinetic performance of the final negative electrode material.

[0046] In one embodiment, the carbonization process is carried out under inert gas conditions. The inert gas is at least one selected from helium, neon, argon, krypton, and xenon.

[0047] In one embodiment, the carbonization temperature is 1200–1500℃, for example, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, etc., the heating rate is 3–5℃ / min, for example, 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min, etc., and the holding time is 2–5h, for example, 2h, 2.5h, 3h, 4h, 5h, etc. By appropriately coordinating the carbonization temperature, time, and heating rate, the carbonized material is ensured to have a specific microstructure, which is beneficial to the electrochemical performance of the final negative electrode material.

[0048] In one embodiment, after the carbonization treatment, the process further includes cooling the carbonized material to room temperature (18-25°C). The cooling is performed using natural cooling.

[0049] In one embodiment, the heat treatment is performed under inert gas conditions. The inert gas is at least one selected from helium, neon, argon, krypton, and xenon.

[0050] In one embodiment, the carbon source includes at least one selected from carbon black, conductive graphite, VGCF, carbon nanotubes, graphene, and acetylene black. In one embodiment, the carbon source is selected from any one of carbon black, conductive graphite, VGCF, carbon nanotubes, graphene, and acetylene black. In one embodiment, the carbon source is selected from at least two of carbon black, conductive graphite, VGCF, carbon nanotubes, graphene, and acetylene black, each in equal mass. In one embodiment, the carbon source is selected from carbon black, conductive graphite, and carbon nanotubes, with a mass ratio of carbon black, conductive graphite, and carbon nanotubes of 1:1:1. In one embodiment, the carbon source is selected from graphene and acetylene black, with a mass ratio of graphene to acetylene black of 1:1.

[0051] According to another aspect of the present invention, the present invention also relates to a pre-sodium-modified hard carbon anode material, which is prepared by the above-described method for preparing pre-sodium-modified hard carbon anode materials.

[0052] The pre-sodium-modified hard carbon anode material of the present invention has excellent conductivity and kinetic properties.

[0053] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the presodium-modified hard carbon negative electrode material prepared by the aforementioned method for preparing presodium-modified hard carbon negative electrode material, or the aforementioned presodium-modified hard carbon negative electrode material.

[0054] According to another aspect of the invention, the invention also relates to a battery comprising the aforementioned negative electrode.

[0055] The battery of the present invention has excellent initial efficiency, cycle performance and kinetic performance.

[0056] The following explanation, combined with specific embodiments and comparative examples, further illustrates the point.

[0057] Example 1

[0058] A method for preparing a pre-sodium-modified hard carbon anode material includes the following steps:

[0059] 1) Pour 150g of phenolic resin and 500mL of ethanol into a beaker, stir at room temperature for 3 hours to mix evenly, and put the evenly mixed solution into an oven for a solvothermal reaction at 150℃ for 2 hours to cure the resin.

[0060] 2) Based on the mass percentage W of oxygen-containing functional groups of the phenolic resin in step 1) determined by XPS testing, the cured phenolic resin and sodium biphenyl were added to a ball mill and ball-milled at 300 r / min for 1 h to obtain a homogeneous precursor.

[0061] 3) The prepared precursor was loaded into a graphite crucible and placed in a tube furnace. It was then carbonized at high temperature under an argon atmosphere. The carbonization temperature was 1500℃, the heating rate was 5℃ / min, the holding time was 3h, and the carbonized material was obtained after natural cooling to room temperature.

[0062] 4) The obtained carbonized material powder is placed in a vapor deposition spiral furnace and heat-treated under the protection of argon gas and graphene gas. The heat treatment temperature is 700℃ and the heat treatment time is 3h to obtain graphene-coated pre-sodium hard carbon anode material.

[0063] The SEM image of the negative electrode material in this embodiment is as follows: Figure 1 As shown.

[0064] Example 2

[0065] A method for preparing a pre-sodium-modified hard carbon anode material includes the following steps:

[0066] 1) Pour 150g of furfural resin and 500mL of ethanol into a beaker, stir at room temperature for 3 hours to mix evenly, and put the evenly mixed solution into an oven and let it undergo a solvothermal reaction at 150℃ for 3 hours to cure the resin.

[0067] 2) Based on the mass percentage W of oxygen-containing functional groups of furfural resin in step 1) determined by XPS test, the cured furfural resin and sodium benzoate were added to a ball mill and ball-milled at 300 r / min for 1 h to obtain a uniformly mixed precursor.

[0068] 3) The prepared precursor was loaded into a graphite crucible and placed in a tube furnace. It was then carbonized at high temperature under an argon atmosphere. The carbonization temperature was 1300℃, the heating rate was 5℃ / min, the holding time was 3h, and the carbonized material was obtained after natural cooling to room temperature.

[0069] 4) The obtained carbonized material powder is placed in a vapor deposition spiral furnace and heat-treated under the protection of argon gas and carbon nanotube gas. The heat treatment temperature is 800℃ and the heat treatment time is 5h to obtain carbon nanotube-coated pre-sodium hard carbon anode material.

[0070] Example 3

[0071] A method for preparing a pre-sodium-modified hard carbon anode material includes the following steps:

[0072] 1) Pour 100g of urea-formaldehyde resin and 500mL of ethanol into a beaker, stir at room temperature for 3 hours to mix evenly, and put the evenly mixed solution into an oven and let it undergo a solvothermal reaction at 120℃ for 3 hours to cure the resin.

[0073] 2) Based on the mass percentage W of oxygen-containing functional groups of urea-formaldehyde resin in step 1) determined by XPS testing, the cured urea-formaldehyde resin and sodium conjugated aromatic diamine were added to a ball mill and ball-milled at 500 r / min for 2 h to obtain a homogeneous precursor.

[0074] 3) The prepared precursor was loaded into a graphite crucible and placed in a tube furnace. It was then carbonized at high temperature under an argon atmosphere. The carbonization temperature was 1400℃, the heating rate was 3℃ / min, the holding time was 3h, and the carbonized material was obtained after natural cooling to room temperature.

[0075] 4) The obtained carbonized material powder is placed in a vapor deposition spiral furnace and heat-treated under the protection of argon gas and conductive carbon black gas. The heat treatment temperature is 900℃ and the heat treatment time is 4h to obtain carbon-coated pre-sodium hard carbon anode material.

[0076] Example 4

[0077] A method for preparing a pre-sodium-modified hard carbon anode material includes the following steps:

[0078] 1) Pour 100g of furan resin and 500mL of ethanol into a beaker, stir at room temperature for 3 hours to mix evenly, and put the evenly mixed solution into an oven and let it undergo a solvothermal reaction at 150℃ for 3 hours to cure the resin.

[0079] 2) Based on the mass percentage W of oxygen-containing functional groups of furan resin in step 1) determined by XPS test, the cured furan resin and sodium conjugated aromatic diamine were added to a ball mill and ball-milled at 300 r / min for 1 h to obtain a precursor.

[0080] 3) The prepared precursor was loaded into a graphite crucible and placed in a tube furnace. It was then carbonized at high temperature under an argon atmosphere. The carbonization temperature was 1300℃, the heating rate was 5℃ / min, the holding time was 3h, and the carbonized material was obtained after natural cooling to room temperature.

[0081] 4) The obtained carbonized material powder is placed in a vapor deposition spiral furnace and heat-treated under the protection of argon gas and VGCF gas. The heat treatment temperature is 900℃ and the heat treatment time is 3h to obtain carbon-coated pre-sodium hard carbon anode material.

[0082] Example 5

[0083] A method for preparing a pre-sodium-modified hard carbon anode material includes the following steps:

[0084] 1) Pour 100g of epoxy resin and 500mL of ethanol into a beaker, stir at room temperature for 3 hours to mix evenly, and put the evenly mixed solution into an oven and let it undergo a solvothermal reaction at 150℃ for 3 hours to cure the resin.

[0085] 2) Based on the mass percentage W of oxygen-containing functional groups in the epoxy resin in step 1) determined by XPS testing, the cured epoxy resin and sodium naphthalene were added to a ball mill and ball-milled at 300 r / min for 1.5 h to obtain a homogeneous precursor.

[0086] 3) The prepared precursor was loaded into a graphite crucible and placed in a tube furnace. It was then carbonized at high temperature under an argon atmosphere. The carbonization temperature was 1300℃, the heating rate was 5℃ / min, the holding time was 3h, and the carbonized material was obtained after natural cooling to room temperature.

[0087] 4) The obtained carbonized material powder is placed in a vapor deposition spiral furnace and heat-treated under the protection of argon gas and acetylene black gas. The heat treatment temperature is 800℃ and the heat treatment time is 2h to obtain carbon-coated pre-sodium hard carbon anode material.

[0088] The mass percentage of oxygen-containing functional groups in each resin and the mass of sodium-based compound added in Examples 1 to 5 are shown in Table 1 below.

[0089] Table 1. Mass percentage of oxygen-containing functional groups in each resin and mass of sodium-based compound added.

[0090]

[0091] Comparative Example 1

[0092] A method for preparing hard carbon includes the following steps:

[0093] 1) Pour 150g of phenolic resin and 500mL of ethanol into a beaker, stir at room temperature for 3 hours to mix evenly, and put the evenly mixed solution into an oven and solvothermal reaction at 150℃ for 2 hours to cure the resin.

[0094] 2) Add the cured phenolic resin to a ball mill and ball mill at 300 r / min for 5 h to mix evenly and obtain the precursor;

[0095] 3) The prepared precursor was loaded into a graphite crucible and placed in a tube furnace. It was then carbonized at high temperature under an argon atmosphere. The carbonization temperature was 1500℃, the heating rate was 5℃ / min, the holding time was 3h, and the hard carbon anode material was obtained after natural cooling to room temperature.

[0096] The SEM image of the negative electrode material in this comparative example is shown below. Figure 2 As shown.

[0097] Comparative Example 2

[0098] A method for preparing hard carbon includes the following steps:

[0099] 1) Pour 150g of furfural resin and 500mL of ethanol into a beaker, stir at room temperature for 3 hours to mix evenly, and put the evenly mixed solution into an oven and let it undergo a solvothermal reaction at 150℃ for 3 hours to cure the resin.

[0100] 2) Add the cured furfural resin to a ball mill and ball mill at 300 r / min for 2 h to mix evenly and obtain the precursor;

[0101] 3) The prepared precursor was loaded into a graphite crucible and placed in a tube furnace. It was then carbonized at high temperature under an argon atmosphere. The carbonization temperature was 1300℃, the heating rate was 5℃ / min, the holding time was 3h, and the material was naturally cooled to room temperature to obtain the hard carbon anode material.

[0102] Comparative Example 3

[0103] The preparation method of the negative electrode material is the same as in Example 1, except that step 4) is not performed.

[0104] Comparative Example 4

[0105] The preparation method of the negative electrode material is the same as in Example 1, except that M1 is 25g, M2 is 150g, W is 55%, T is 700℃, H is 3h, and M1-(M2*0.2*H*W / (lgT-1))=-2.

[0106] Experimental Example

[0107] Weigh 100g of each of the materials prepared in Examples 1-5 and Comparative Examples 1-4. Mix the hard carbon sample, CMC, and SBR in a mass ratio of 92:3:3:2 and grind them thoroughly. Then, evenly coat the prepared electrode slurry onto the treated aluminum foil and place it in a vacuum drying oven. Dry it under vacuum at 80°C for 24 hours and weigh it. Wrap the dried electrode sheet with clean aluminum foil from top to bottom and place it in a flat, rigid, and clean stainless steel mold. Press it under a pressure of 10MPa to obtain the sample electrode sheet. In a glove box, take out the negative electrode shell, put in the spring and the gasket in sequence, drop a drop of electrolyte on the gasket with a pipette, place the sodium sheet on the gasket, drop a drop of electrolyte on the sodium sheet, place the separator, and drop electrolyte on the separator until the separator is completely wetted. Then, place the negative electrode sheet (with the active material side facing the separator) and the positive electrode shell in sequence. Assemble the coin half cell in a glove box filled with argon gas. The batteries from Examples 1-5 and Comparative Examples 1-4 were subjected to charge-discharge performance tests: using the LAND battery testing system, charge-discharge performance tests were conducted at a rate of 0.5, and their capacity, initial efficiency, coin cell DCR / EIS, cycle life, and rate performance were tested respectively. The results are shown in Tables 2 and 3.

[0108] Table 2. Charge and discharge performance test results

[0109]

[0110] Table 3. Button Cell DCR / EIS Test Results

[0111]

[0112] As shown in Table 2, the batteries obtained in Examples 1 to 5 of the present invention have higher initial charge-discharge efficiency and better cycle performance than the batteries obtained in Comparative Examples 1 to 4.

[0113] As shown in Table 3, the batteries obtained in Examples 1-5 of the present invention have lower coin cell DCR / EIS, better charging capacity, and superior rate performance compared with the batteries obtained in Comparative Examples 1-4.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a pre-sodium-modified hard carbon anode material, characterized in that, Includes the following steps: The resin and alcohol solvent are mixed and heated to obtain a cured resin; the cured resin and sodium-based compound are ball-milled to obtain a precursor; the precursor is carbonized to obtain a carbonized material; the mixture of the carbonized material and the carbon source is heat-treated to obtain a pre-sodium-modified hard carbon anode material; the carbon source includes at least one of carbon black, conductive graphite, VGCF, carbon nanotubes, graphene, and acetylene black. The mass of the sodium-based compound is M1g, the mass of the resin is M2g, the mass percentage of oxygen-containing functional groups in the resin is W, the heat treatment temperature is T℃, and the heat treatment time is Hh. M1, M2, W, T, and H satisfy the following relationship: 0 ≤ M1 - (M2) / (W / H). 0.2 H W / (lgT-1))≤5, where 20%≤W≤80%, 600≤T≤900, and 1≤H≤5.

2. The method for preparing the pre-sodium-modified hard carbon anode material according to claim 1, characterized in that, It includes at least one of the following features (1) to (3): (1) The resin includes at least one of epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, melamine-formaldehyde resin, furan resin, polyamide resin, acrylic resin, polyurethane and vinyl resin; (2) The sodium-based compound includes at least one of sodium naphthalene, sodium biphenyl, sodium phenanthrene, sodium benzophenone, disodium terephthalate, and sodium conjugated aromatic diamine; (3) The ratio of the amount of resin to the amount of alcohol solvent is (100~200) g: (480~520) mL.

3. The method for preparing the pre-sodium-modified hard carbon anode material according to claim 1, characterized in that, It includes at least one of the following features (1) to (2): (1) The mixing time is 3~5h; (2) The heating temperature is 150~180℃ and the heating time is 2~6h.

4. The method for preparing the pre-sodium-modified hard carbon anode material according to claim 1, characterized in that, The ball milling process is carried out at a rotation speed of 200~600 r / min and for a duration of 1~2 h.

5. The method for preparing the pre-sodium-modified hard carbon anode material according to claim 1, characterized in that, It includes at least one of the following features (1) to (3): (1) The carbonization process is carried out under inert gas conditions; (2) The carbonization temperature is 1200~1500℃, the heating rate is 3~5℃ / min, and the holding time is 2~5h; (3) After the carbonization treatment, the carbonized material is further cooled to room temperature.

6. The method for preparing the pre-sodium-modified hard carbon anode material according to claim 1, characterized in that, The heat treatment is carried out under inert gas conditions.

7. A pre-sodium-modified hard carbon anode material, characterized in that, It is prepared by the method for preparing pre-sodium-modified hard carbon anode material according to any one of claims 1 to 6.

8. A negative electrode sheet, characterized in that, The presodium hard carbon anode material prepared by the method described in any one of claims 1 to 6, or the presodium hard carbon anode material as described in claim 7.

9. A battery, characterized in that, Includes the negative electrode sheet as described in claim 8.

Citation Information

Patent Citations

  • Hard carbon negative electrode composite material and preparation method and application thereof

    CN113184827A

  • Sodium-ion battery hard carbon negative electrode material and preparation method thereof

    CN116022769A